БІФУРКАЦІЯ ПЕРІОДИЧНИХ РОЗВ’ЯЗКІВ У ПАРАБОЛІЧНИХ СИСТЕМАХ ІЗ МАЛОЮ ДИФУЗІЄЮ - Клевчук, Іван; Гритчук, Микола (Чернівецький національний університет імені Юрія Федьковича, 2022)
We prove the existence of periodic solutions in autonomous parabolic system of differential equations with weak diffusion on the circle. We consider the problem of existence and stability of traveling waves. We study the existence and stability of an arbitrarily large finite number of cycles for a parabolic system with weak diffusion.
Міжнародна науково-практична конференція "Молодіжна наука заради миру та розвитку"
Keywords: parabolic system, bifurcation, integral manifold, stability, traveling waves.